2011
DOI: 10.1073/pnas.1110030108
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzias an effective cancer antigen delivery vector

Abstract: One of the main challenges in cancer research is the development of vaccines that induce effective and long-lived protective immunity against tumors. Significant progress has been made in identifying members of the cancer testis antigen family as potential vaccine candidates. However, an ideal form for antigen delivery that induces robust and sustainable antigen-specific T-cell responses, and in particular of CD8 + T lymphocytes, remains to be developed. Here we report the use of a recombinant nonpathogenic cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 50 publications
1
43
0
3
Order By: Relevance
“…Nonpathogenic live parasites, such as Leishmania tarentolae , T. gondii and T. cruzi are emerging as novel candidates for gene delivery in anticancer therapeutic approaches . In fact, it was found that a recombinant nonpathogenic clone of T. cruzi expressing a cancer testis antigen (NY‐ESO‐1) induces antigen‐specific T‐cell responses and effective protection against tumors in a mouse model . The use of T. cruzi ‐derived TLR agonists as immunological adjuvants also resulted in a significant delay in the growth of the B16‐F10 melanoma cell line expressing NY‐ESO‐1 antigen .…”
Section: Discussionmentioning
confidence: 99%
“…Nonpathogenic live parasites, such as Leishmania tarentolae , T. gondii and T. cruzi are emerging as novel candidates for gene delivery in anticancer therapeutic approaches . In fact, it was found that a recombinant nonpathogenic clone of T. cruzi expressing a cancer testis antigen (NY‐ESO‐1) induces antigen‐specific T‐cell responses and effective protection against tumors in a mouse model . The use of T. cruzi ‐derived TLR agonists as immunological adjuvants also resulted in a significant delay in the growth of the B16‐F10 melanoma cell line expressing NY‐ESO‐1 antigen .…”
Section: Discussionmentioning
confidence: 99%
“…Further to the anticancer properties, T. cruzi is an effective cancer antigen delivery vector (Junqueira et al, 2011). A study utilized the attenuated T. cruzi CL-14 clone to express exogenously a cancer testis antigen (NY-ESO-1) and showed that T. cruzi parasites expressing NY-ESO-1 were able to induce strong NY-ESO-1 specific immune responses both in-vitro and in-vivo .…”
Section: Paradoxical Dual Impacts Of Chagas Disease In Carcinogenesismentioning
confidence: 99%
“…A study utilized the attenuated T. cruzi CL-14 clone to express exogenously a cancer testis antigen (NY-ESO-1) and showed that T. cruzi parasites expressing NY-ESO-1 were able to induce strong NY-ESO-1 specific immune responses both in-vitro and in-vivo . Interestingly, immunization with T. cruzi parasites expressing NY-ESO-1 would lead to an effective immune response to kill tumor cells and to inhibit tumor development (Junqueira et al, 2011). Taken together, T. cruzi may exert both carcinogenic and antitumor effects (Fig.…”
Section: Paradoxical Dual Impacts Of Chagas Disease In Carcinogenesismentioning
confidence: 99%
“…Recently, a recombinant non-pathogenic clone of Trypanosoma cruzi expressing a cancer testis antigen (NY-ESO-1) has been used as a vaccine vector to induce long-term T cell-mediated immunity and delay the rate of tumor development in mice (Junqueira et al, 2011).…”
Section: Discussionmentioning
confidence: 99%